Analisis Kepatuhan Karyawan di PT XYZ - Windhy Febrianty; Christian Wiradendi Wolor; Eka Dewi Utari (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the degree of employee compliance with the Standard Operating Procedures (SOP) at PT XYZ, especially in the implementation of working hours. The background of this study was based on the findings of a discrepancy between practices in the field and the company's SOP provisions, such as delays in employees entering work and unscheduled return. This study used a descriptive qualitative method with a case study approach. Data collection techniques are carried out through observation, interviews, and documentation of PT XYZ's employees and HRD. The factors that hinder compliance include lack of personal discipline, distance of residence, lack of supervision, and low understanding of SOPs. Failure to comply with the SOP has resulted in a decline in performance, administrative sanctions, and potential loss of company operations. Research results show that while companies have clear disciplinary enforcement policies and procedures, better strategies are needed to improve employee awareness and discipline in complying with standard operational procedures (SOPs). This study emphasizes the importance of improving SOP understanding through training as well as strengthening supervisory policies to create a work culture that is disciplined and compliant with applicable rules.